Neutron scattering studies of some unconventional magnets - Welch, PG (2021)
The identification and characterisation of low-dimensional and frustrated magnetic systems is an area of great importance in the field of solid-state chemistry. If we intend to design and control the magnetic properties of frustrated magnets, we must first understand the microscopic interactions responsible for the formation of these disordered magnetic phases. This is of fundamental interest due to the potential for frustrated magnets to form e.g. quantum spin liquid materials. Frustrated and low-dimensional phases are not solely of fundamental interest; a number of properties have been identified as stemming directly, or indirectly, from disordered magnetic states. Correlated magnetic disorder has been implicated in the formation of, for example, high-temperature superconducting, multiferroic, and magnetocaloric systems. The analysis of neutron scattering is of pivotal importance in understanding such systems. In disordered phases, we cannot rely on Bragg peaks in neutron scattering patterns, since the long-range order is suppressed by frustration. Instead we must turn to the diffuse magnetic neutron scattering created by local, short-range, correlations. In this thesis I present investigations of several frustrated and low-dimensional magnetic systems using a variety of neutron scattering techniques. In Chapters 3 and 4 I explore the structures of two triangular lattice antiferromagnets, CsCoCl₃ and the metal-organic framework Tb(HCO₂)₃. In Chapter 5 I present the first neutron scattering investigation of Gd₂Pt₂O₇; a recently reported magnetic pyrochlore system. I have employed both polarised diffuse neutron scattering and inelastic neutron scattering measurements in order to quantify the microscopic interactions which serve to relieve the frustration, relative to other gadolinium pyrochlores. Finally, in Chapter 6, I have investigated the spin-chain compound Er₂BaNiO₅ using a combination of single-crystal neutron diffraction, and bulk magnetic and electrical property measurements.